The theory of electron states on the dynamically deformed adsorbed surface of a solid - Peleshchak, R.M.; Seneta, M.Ya. (Condensed Matter Physics, 2018)
Dispersion relations for the spectra of surface electron states on a dynamically deformed adsorbed surface of a
monocrystal with the Zinc blende structure are received. It is established that the dependences of the band gap
width and of the concentration of electrons on the concentration of adatoms N0d upon the solid surface are of
nonmonotonous character Отримано дисперсiйнi спiввiдношення для спектру поверхневих електронних станiв на динамiчно деформованiй адсорбованiй поверхнi монокристалу зi структурою цинкової обманки. Встановлено, що залежностi ширини забороненої зони та концентрацiї електронiв на поверхнi твердого тiла вiд концентрацiї адсорбованих атомiв N0d мають немонотонний характер